Shore assessment at the gravel pit ponds of Délegyháza - Sallay, Ágnes; Boromisza, Zsombor (JOURNAL OF LANDSCAPE ECOLOGY, 2011)
In the framework of a professional co-operation initiated by the Environment Protection Information Club Nonprofit Association (abbreviation of its Hungarian name: KVIK), it was the Middle Danube Valley Inspectorate for Environmental Protection, Nature Conservation and Water Management, as well as the Departments of Landscape Preservation and Reclamation and of Landscape Planning and Regional Development of Corvinus University of Budapest, which began to assess the shore-zone of the gravel pit ponds at Délegyháza in May 2009. The first assessment was made on the gravel pit pond No. I. (Lake Gizella), followed by that of the lake No. V. in September 2009, whereas the students make survey of a shore-zone of pond No. II. in the semesters of 2010-2011.Délegyháza has 300 ha water-surface on its territory disposing of a recreational potential that has not been utilized so far. The great part of the area consists of the lake-system, the neighbouring water-shore associations as well as of the sand-, gravel- and dead rock piles, taken out during mining. The landscape and natural potentials of shore zones significantly define the ecological condition and utilisation opportunities of standing waters, yet, monitoring of these zones are often played down compared to the processes in the water-body and the catchment research. Having in mind the functions that determine the condition of the whole water body (e.g. special habitat, bio filter- and mechanical protection’ function of the near nature riparian vegetation, attracting factor of tourism, place to reach the water-body, etc.), and the procedures influencing same ( e.g. fluctuating water level, shore-regulation, built-in area, obliteration of marshland vegetation, erosion) it is absolutely necessary to create shore-zones with conscious, purposeful and complex approach. To establish a proper basis for the planning, landscaping, and management, an investigation and evaluation methodology is needed by which the special features of the shores can be revealed and further decisions can be founded.
Keywords: habitat assessment; landscape planning; landscape preservation; environmental protection; lakeshore zone